Necrotizing fasciitis in children: Experience in a teaching hospital - Bhat, Kamalakshi G.; Shenoy, Rathika D.; Kamath, Nutan (Journal of Pediatric Infectious Diseases, 2007)
Necrotizing fasciitis is a bacterial infection of the soft tissues with a fulminant course and a high mortality rate. It is rare in children and early recognition with aggressive treatment can help in improving the survival in these cases. During the study period 12 children with mean age of 35 months developed necrotizing fasciitis. Common initiating factors observed were varicella infection and minor injury. The trunk was the most common site of involvement. Tissue culture was positive in 10 cases, of which three were polymicrobial. Blood cultures were positive in three cases. Staphylococcus aureus was the most common pathogen. All the cases were treated with parenteral antibiotics and 10 cases required surgical intervention. Complications included thrombocytopenia, shock, acute renal failure, septicemia, disseminated intravascular coagulation and multiorgan failure. Two patients died (mortality rate 16.7%). Early diagnosis and aggressive treatment in a Pediatric Intensive Care Unit may have contributed to decreased mortality compared with earlier studies.
Keywords: Necrotizing fasciitis; Staphylococcus aureus; children